The role of fibroblast growth factor receptor-3 as a negative regulator in late mandibular growth: Peran fibroblast growth factor receptor-3 sebagai regulator negatif di akhir pertumbuhan mandibula - Pratiwi, Dwita; Suniarti, Dewi Fatma; Soedarsono, Nurtami; Soegiharto, Benny M. (Makassar Dental Journal PDGI Makassar, 2025)
Assessment of mandibular growth status has been done using cephalometric radiographs by looking at cervical bone maturation. Recent studies suggest that this method is not good at identifying the final period of growth. In recent years, biomolecular re-search has been conducted to look at the potential of proteins as growth indicators. It is important to comprehensively understand the mandibular growth process in order to determine which proteins have the potential to be used as indicators. Mandibular growth is a complex biological process that is regulated by various proteins through various signalling pathways. The centre of growth is at the mandibular condyle which has a unique cartilage and plays a dual role as articular cartilage and growth plate. This review discusses the role of fibroblast growth factor receptor-3 (FGFR-3) in the mandibular growth process and its signalling pathways. The FGFR-3 was shown to act as a negative regulator of mandibular growth by reducing the proliferation and hypertrophic dif-ferentiation of chondrocytes in mandibular condylar cartilage. It is concluded that the regulation of FGFR-3 is localised due to pre-vious studies on condylar cartilage of experimental animals, so further research needs to be done to see the role of FGFR-3 in human mandibular growth.